Penerapan metode pembelajaran cooperative integrated reading composition (CIRC) berbasis media flipbook dalam meningkatkan membaca pemahaman Siswa - Fitria, Alami (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was motivated by the low interest in reading and the results of students' reading comprehension skills in story text material for students in class VI UPT SD Negeri 05 Nanggalo. The solution to overcome this problem is to add flipbook learning media and apply the CIRC model. The aim of this research is to increase students' interest in reading and improve students' reading comprehension skills in material texts. This research design uses Classroom Action Research. This research was conducted in two cycles, each cycle consisting of two meetings. The subjects of this research consisted of 22 students. Data collection in this research used a test question instrument. Based on the results of the analysis, it can be seen that the use of media as a tool for learning increases students' interest in reading and there is an increase in students' reading comprehension skills in Indonesian language lessons. The achievement was only 45.5% in cycle I, meeting I, experienced a slight increase of 59.1% in cycle I, meeting II, and in cycle II, meeting I, it increased to 81.8%, then increased to 86.4% in cycle II, meeting II, Therefore, it can be concluded that students' reading interest and reading ability of class VI UPT SD Negeri 05 Nanggalo students can be improved by using Flipbook learning media and using the Cooperative Integrated Reading and Composition (CIRC) model.